COMPREHENSIVE MANAGEMENT OF ORAL CANDIDIASIS IN A PATIENT WITH SEVERE IRON DEFICIENCY ANEMIA (A CASE REPORT) - Yohana Gowara; Gus Permana Subita (Faculty of Dentistry, Universitas Indonesia, 2006)
Oral candidiasis, the most common opportunistic oral fungal infection in human is mainly caused by Candida albicans. Predisposing factors in the disease include immunosuppression, medications, malignancies, endocrine disorders, nutritional deficiencies, high-carbohydrate diet, salivary changes, dental prostheses, smoking and poor oral hygiene. We report a case of oral candidiasis with severe iron deficiency anaemia as an underlying factor, in a 40 year old male patient, based on the history, clinical findings, and fungal examinations. Case management included prescribing anti-fungal agent, identification and correction of predisposing factors and elimination of oral fungal reservoir. The oral lesions were reduced with improving systemic condition. We concluded that comprehensive management is required to achieve an optimal improvement in this case.